Institutional change and the political economy of water megaprojects: China's south-north water transfer. (May 2016) - Pohlner, Huw
Highlights: First-look assessment of institutions for managing world's newest water megaproject. Maps government actors involved in South-North Water Transfer (Middle Route). Analyses effectiveness of SNWT-MR pricing, financing and compensation institutions. Water megaprojects demand institutional change. Abstract: This paper analyses the relationship between megaproject construction and change in water management institutions. Due to the wide geographical distribution of their costs and benefits, which often spans national and provincial borders, water supply megaprojects frequently prompt intentional or evolutionary institutional change. China's South-North Water Transfer Project (Middle Route), the world's largest interbasin transfer project, was completed in December 2014 and is now in operation. Based on extensive fieldwork and analysis of Chinese documents, this paper introduces the government actors involved in, and impacted by, the planning and construction of the project. By detailing the interests of these actors, and the way those interests have been affected by the political, economic and environmental changes wrought by the megaproject, it shows that the Middle Route project has already contributed to change in one major financial institution – water pricing – and is exerting pressure on at least two others—infrastructure financing and compensation. Despite the regulatory efforts of the Chinese central government, incomplete institutional change processes threaten the long-term viability of the megaproject. Megaprojects demand institutional change and this must be factored into policymaking processes; business as usual will not suffice if the real benefits of the South-North Water Transfer are to be fairly distributed and its negative social, economic and environmental effects mitigated and appropriately compensated.